Multitude and Resistance in the Framework of the Contemporary “Empire”, According to Antonio Negri and Michael Hardt - Bonilla Elizondo, Pablo (2021)
This paper addresses the theories developed by Antonio Negri y Michael Hardt about the contemporary Global Empire, the new political subjects and the forms of resistance that operate in it. These forms of resistance are presented consistent with the epistemological transformations that has undergone art in recent decades, which have redefined their practices and their links with politics. It is concluded that the interweaving between art and political activism –unlike modernist couplings– allows us to glimpse the potential and relevance of contemporary art for the continuous construction and defense of a democratic, solidary and equitable society in the current panorama.